PENGEMBANGAN BAHAN AJAR BERBASIS KOMIK PADA MATERI HIDUP BERSAMA ALAM UNTUK MENINGKATKAN HASIL BELAJAR SISWA KELAS IIIC SD INPRES LASIANA KOTA KUPANG - Adi Laksari Balu; E. Noya Nahak, Kristina; Tua, Siprianus (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Comic-based teaching materials have an important role in learning activities. The existence of this teaching material is expected to be used by teachers and students at SD Inpres Lasiana to increase students' knowledge and learning outcomes in the subject of science and natural sciences. The purpose of this study is to determine the feasibility, practicality, and effectiveness of comic teaching materials to improve student learning outcomes in the subject of science and natural sciences in class IIIC SD Inpres Lasiana that have been made. The type of research used in this study is development research using the Research and Development (R&D) method with the ADDIE development model (Analyze, Design, Develop, Implement, and Evaluate) and the number of samples in class IIIC SD Inpres Lasiana students totaling 21 people, with instruments in the form of expert validation questionnaires, teacher and student response questionnaires, and learning outcome tests. Based on the study, it shows that comic teaching materials received very good assessments from material experts (99%), media experts (97%), language experts (95%), teacher responses (96.25%), and student responses (90.40%). Student learning outcomes also improved significantly, with an average pretest score of 41% rising to 91% in the posttest (very good) category. A gain test score of 0.85 (>0.7) indicated an increase in the (high) category. This study concluded that comic-based teaching materials are effective and can be an innovative alternative in science learning in elementary schools, particularly in the topic of living in nature.